32 & 16 YEARS AGO. (Computer (00189162), 2007)
The article reprints excerpts from article that appeared in issues of the magazine in the August 1975 issue and in the edition dating from August 1991. A number of topics are covered in the earlier issue including advances in microprogramming computers, the introduction of a pocket calculator and an increase in the capacity of memory chips. In 1991 the magazine published articles on memory card capacity, computer system design and applications, and protection from viruses. The excerpts are meant to be nostalgic or risible.